2006
DOI: 10.1083/jcb.200601113
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupling global and fine-tuning replication timing determinants for mouse pericentric heterochromatin

Abstract: Mouse chromocenters are clusters of late-replicating pericentric heterochromatin containing HP1 bound to trimethylated lysine 9 of histone H3 (Me3K9H3). Using a cell-free system to initiate replication within G1-phase nuclei, we demonstrate that chromocenters acquire the property of late replication coincident with their reorganization after mitosis and the establishment of a global replication timing program. HP1 dissociated during mitosis but rebound before the establishment of late replication, and removing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
74
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(85 citation statements)
references
References 66 publications
(116 reference statements)
11
74
0
Order By: Relevance
“…Depletion of HP1 could result in the loss of the requirement for this mechanism and therefore allow slightly earlier replication of centromeric repetitive heterochromatin. This advanced replication timing of repeats is consistent with observations in mouse fibroblasts, where replication timing of centromeric repeats is advanced in cells depleted of the mouse homologs of the Drosophila histone methyltransferase SU(VAR)3-9 that methylate lysine 9 on histone H3 (Wu et al 2006). Interestingly, however, embryonic stem cells lacking the SUV39H1 and SUV39H2 H3K9 methyltransferases showed delayed replication timing of centromeric repeats (Jorgensen et al 2007), underscoring the context dependency of the interaction between chromatin and the replication timing program.…”
Section: Replication Timing Of Centromeric Repeats Is Advanced After supporting
confidence: 74%
“…Depletion of HP1 could result in the loss of the requirement for this mechanism and therefore allow slightly earlier replication of centromeric repetitive heterochromatin. This advanced replication timing of repeats is consistent with observations in mouse fibroblasts, where replication timing of centromeric repeats is advanced in cells depleted of the mouse homologs of the Drosophila histone methyltransferase SU(VAR)3-9 that methylate lysine 9 on histone H3 (Wu et al 2006). Interestingly, however, embryonic stem cells lacking the SUV39H1 and SUV39H2 H3K9 methyltransferases showed delayed replication timing of centromeric repeats (Jorgensen et al 2007), underscoring the context dependency of the interaction between chromatin and the replication timing program.…”
Section: Replication Timing Of Centromeric Repeats Is Advanced After supporting
confidence: 74%
“…Thus, we hypothesize that a key G 1 -phase event exists during epiblast development, in which a significantly altered subnuclear repositioning pattern is observed compared with G 1 in prior cell cycles. While it is tempting to speculate the roles of chromatin modifying activities in this genome reorganization process, we and others have shown that ablation of several chromatin modifying enzymes (MLL1 [also known as MLL], MBD3, EED, SUV39H1/H2, EHMT2 [also known as G9a], DNMT1/3A/3B, DICER) show only modest effects on replication timing (Wu et al 2006;Jorgensen et al 2007;Yokochi et al 2009). Moreover, the few known DNA methylation events, such as on the Pou5f1 promoter and the Xi, are downstream (Lock et al 1987;Feldman et al 2006).…”
Section: Loss and Gain Of Pluripotency: An Epigenetic Barriermentioning
confidence: 99%
“…We exploited the fact that MEFs show cytologically defined Sphase stages that are easily distinguished by characteristic spatiotemporal patterns of DNA synthesis (Quivy et al, 2004;Wu et al, 2006) to determine whether altered replication in RING1A-and RING1B-deficient cells affected such patterns. We used asynchronous MEF cultures, 48 h after EtOH or 4′-OHT treatment, and pulsed them with IdU for 20 min in order to score the proportion of cells in each of the S-phase stages.…”
Section: Ink4amentioning
confidence: 99%